ANALISIS PERTANGGUNGJAWABAN NOTARIS SETELAH BERAKHIR JABATANNYA - Soedagoeng, Gembongseto Hendro; Hazilina, Hazilina (Res Judicata, 2020)
ABSTRACTNotary as a public official of the State who is given the authority by law to make authentic deeds and other powers with the limitation that the deed made is not excluded from making it to other officials who are determined by law the notary's responsibility for the deeds that have been drawn up before him and / or by a Notary while carrying out his duties as a Notary, is until the end of his life or death, thus Article 65 of Law no. 2 of 2014 concerning Amendments to Law no. 30 of 2004 concerning the Position of Notary this must be read as such because there is no further  explanation in  the  explanation  of  Law no. 2 of 2014 concerning Amendments to Law no. 30 of 2004 concerning the Position of the Notary PublicThis is important because if the time limit for the said responsibility is not set, it is possible that at old age the Notary will still be asked for information regarding the deeds that have been made while the person concerned is carrying out his duties as a state general official.Arrangements regarding expiry must be taken into consideration to determine the expiry limit of the Notary's responsibility for the deed drawn up before him.Keywords: Notary, Deed, Responsibility ABSTRAKNotaris sebagai pejabat umum Negara yang diberikan wewenang oleh Undang-Undang untuk membuat akta autentik dan kewenangan lainnya dengan batasan bahwa akta yang dibuat tersebut tidak dikecualikan pembuatannya kepada pejabat lain yang ditentukan oleh undang- undang tanggungjawab Notaris terhadap akta-akta yang telah dibuat dihadapannya dan/atau oleh Notaris selama menjalankan tugas menjadi Notaris, adalah sampai akhir hayat atau meninggal dunia, dengan demikian Pasal 65 UU  No. 2 Tahun 2014 Tentang Perubahan Atas UU No. 30 Tahun 2004 Tentang Jabatan Notaris ini harus dibaca demikian karena tidak ada penjelasan lebih lanjut didalam  Penjelasan UU No. 2  Tahun  2014 Tentang Perubahan Atas UU No. 30 Tahun 2004 Tentang Jabatan Notaris tersebut.Hal ini penting karena apabila tidak ditetapkan batas waktu tanggungjawab tersebut, maka tidak menutup kemungkinan diusia tua rentapun Notaris masih akan dimintai keterangan tentang akta-akta yang telah dibuat selama yang bersangkutan melaksanakan tugasnya sebagai pejabat umum negara.Pengaturan tentang kadaluwarsa harus dijadikan bahan pertimbangan untuk menentukan batas berakhirnya pertanggungjawaban Notaris terhadap akta yang dibuat dihadapannya.Kata Kunci: Notaris; Akta; Tanggung jawab